Monosynaptic Input Mapping of Diencephalic Projections to the Cerebrospinal Fluid-Contacting Nucleus in the Rat - Song, Si-Yuan; Li, Ying; Zhai, Xiao-Meng; Li, Yue-Hao; Bao, Cheng-Yi; Shan, Cheng-Jing; Hong, Jia; Cao, Jun-Li; Zhang, Li-Cai (Frontiers in Neuroanatomy, 2020)
Objective: To investigate the projections the cerebrospinal fluid-contacting (CSF-contacting) nucleus receives from the diencephalon and to speculate on functional significance of these connections. Methods: The retrograde tracer cholera toxin B subunit (CB) was injected into the CSF-contacting nucleus in SD rats according to the experimental formula of the stereotaxic coordinates. Animals were perfused 7-10 d after the injection, and the diencephalon was sliced at 40 μm with a freezing microtome. CB-immunofluorescence was performed on all diencephalic sections. The features of CB-positive neuron distribution in the diencephalon were observed with a fluorescence microscope. Results: The retrograde labelled CB-positive neurons were found in the epithalamus, subthalamus and hypothalamus. Three functional diencephalic areas including forty-three sub-regions revealed projections to the CSF-contacting nucleus. The CB-positive neurons were distributed in different density ranges: sparse, moderate, and dense. Conclusion: Based on the connectivity patterns of the CSF-contacting nucleus receives anatomical inputs from the diencephalon, we preliminarily assume that the CSF-contacting nucleus participates in homeostasis regulation, visceral activity, stress, emotion, pain and addiction, and sleeping and arousal. The present study firstly illustrates the broad projections of the CSF-contacting nucleus from the diencephalon, which implies the complicated functions of the nucleus especially for the unique roles of coordination in neural and body fluids regulations.